Kerapatan dan Persebaran Tumbuhan Air di Danau Buyan Kabupaten Buleleng, Provinsi Bali - Sudipta, I Gusti Made; Arthana, I Wayan; Suryaningtyas, Endang Wulandari (Journal of Marine and Aquatic Sciences; Vol 6 No 1 (2020)DO - 10.24843/jmas.2020.v06.i01.p09, 2020)
The Bali province has four lakes, one of them is Buyan lake. One of communities that has important roles in lake waters ecosystem as an primary production is a community of aquatic plants. The existence of aquatic plants as weed will suffer losses more than the beneficial. So that research on density and distribution of aquatic plants in Buyan lake is very important to do. The research aims to find out the density, distribution, domination, percent of closure and other types of aquatic plants in Buyan lake. This research was conducted for 1 month during the month of March until April 2017. The value of the density of the population (KP) aquatic plants has ranged from 2-357 individuals/m 2 . The value of the frequency of attendance (FK) aquatic plants ranging between 0,1-1. Morisita Index (Id) has ranged from 4,9-1,39 which shows a pattern of clumped. The value of Dominance (D) aquatic plants has ranged between 0,0001-0,9823 that showed with its low variation and high abundance. The value of aquantic plant cover has percent range from 1-72% that showed of the vegetation very rare, rare and dense. The aquatic plants found during research had 4 types of living that were type of free float ( Free Floating ) Salvinia molesta , Eichhornia crassipes ( S ubmerged ) Myriophyllum aquaticum , ( F loating ) Alternanthera philoxeroides , sticking ( Emergent ) Schoenoplectus paludicola , Phragmites australis , Typha capensis .